Chromosomes and other prognostic factors in acute lymphoblastic leukaemia: a long-term follow-up. - Secker-Walker, L; Chessells, J; Stewart, E; Swansbury, G; Richards, S; Lawler, S (1989)
Cytogenetic, clinical and laboratory features at diagnosis were examined in a group of 80 children with acute lymphoblastic leukaemia (ALL) who had been followed up for a minimum of 5 1/2 years. The 17 (21%) with high hyperdiploidy tended to have low leucocyte counts and common ALL, but their favourable outcome (75% event-free survival) was independent of these factors. No patient with hypodiploidy survives while the pseudodiploid and normal groups have an intermediate prognosis. Cytogenetic analysis showed examples of patients with the well-recognized translocations and a number with apparently unique ones. Among the latter were some long-term survivors. We conclude that cytogenetic analysis identifies a good risk group of patients who remain well on long-term follow-up, but that the presence of a translocation does not necessarily imply a poor outcome.